TINJAUAN KEANEKARAGAMAN MOLUSKA AIR TAWAR DI BEBERAPA SITU DI DAS CILIWUNG - CISADANE - Ristiyanti M. Marwoto; Nur R. Isnaningsih (BERITA BIOLOGI, 2014)
The freshwater molluscs (snails and bivalves) can be found in many type of water course either flowing or stagnant water. Some of them have survived living in bad condition such as polluted water. There are 199 situ (small lakes) in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) have been reported but only 20 % were in good condition, even 12% have dissapeared that caused by silting up of the situ. The aim of the study was to evaluate the diversity of the molluscs as well as to know the condition of on 36 situ along Ciliwung River and Cisadane River. Based on the collected samples, there were 13 species of snails and three species of bivalves. The freshwater snails Filopaludina javanica, Melanoides tuberculata, Pomacea canaliculata always occur in these situ but the bivalves Anodonta woodiana, Pilsbryoconcha exilis and Corbicula javanica only occur in situ Ciranji and Kemuning along Cisadane and Ciliwung rivers, respectively. The decreasing of the mollusc diversity was about 38% in Ciliwung River and 73% in Cisadane River, caused by polluted and silting up of the situ .